2018
DOI: 10.3126/jpan.v6i2.21763
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use, Dependence and Psychiatric Co-Morbidities Among Patients Admitted in Psychiatry Ward

Abstract: Introduction: Nicotine dependent individuals among the tobacco users are in greater risk of having tobacco related disease and psychiatric co-morbidities. There is little information about the tobacco use and nicotine dependence among psychiatric patients in developing countries including Nepal. This study was done to estimate the prevalence of tobacco use, the level of nicotine dependence among the users and the psychiatric disorder specific prevalence among tobacco users admitted in psychiatry ward.Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This prevalence points towards the extent of the problem in this part of the world. 17,18 A study conducted by Josseran et al 20 in a Paris medical school showed that more than one third of students were smokers (35%); 21% were daily smokers and 14% were occasional smokers which is comparable to this study. Budhathoki N et al 9 have studied substance use among third year Medical students of Nepal and found that about 56.20% of the students used tobacco after joining medical school in comparison to 43.80% consumed tobacco before joining medical school and majority of them were in hostels (53%) and rented house (62.50%).…”
Section: Association Of Cannabis With Socio Demographic Profilesupporting
confidence: 86%
See 1 more Smart Citation
“…This prevalence points towards the extent of the problem in this part of the world. 17,18 A study conducted by Josseran et al 20 in a Paris medical school showed that more than one third of students were smokers (35%); 21% were daily smokers and 14% were occasional smokers which is comparable to this study. Budhathoki N et al 9 have studied substance use among third year Medical students of Nepal and found that about 56.20% of the students used tobacco after joining medical school in comparison to 43.80% consumed tobacco before joining medical school and majority of them were in hostels (53%) and rented house (62.50%).…”
Section: Association Of Cannabis With Socio Demographic Profilesupporting
confidence: 86%
“…Nicotine use doesn't appear to be lower than general population in this region. A study conducted at the department of Psychiatry by Limbu et al reveals that the prevalence of tobacco use was 55.6% in OPD, 17 62.2% in admitted 18 cases and 41.4% in community 19 . Tobacco use was more common among males in all three settings (p value < 0.05).…”
Section: Association Of Cannabis With Socio Demographic Profilementioning
confidence: 99%
“…Some sporadic studies and observation supports this fact; both over all and specific substance data are there to suggest it. As nationwide, this part also has alcohol and nicotine as the most common problem substances both in community and clinical settings [14][15][16][17]. Studies indicate IVDs and opiate to be common and cannabis not less here [14].…”
Section: Substance In Eastern Nepal-mentioning
confidence: 99%
“…Substance problem is also a main clinical entity as is seen in reports from clinical setting of this region. Substance problems, mainly alcohol, though less studied also nicotine/tobacco and others are among main diagnostic category in out-patient [17,18], in-patient and psychiatry emergency services [19].…”
Section: Substance In Eastern Nepal-mentioning
confidence: 99%